Print Magazine Covers as Packaging - Jupowicz-Ginalska, Anna (Communication Today, 2018)
Packaging and magazine covers share many common traits. Both these elements are very important in relation to marketing activities of media and non-media enterprises. And while there are quite a lot of studies on packaging itself, there are not as many in-depth analyses of magazine covers. This article is a part of a series of scholarly texts, in which the author analyses the phenomenon of magazines’ front-pages, aiming to fill a certain scientific void when it comes to research on magazine covers and e-covers. In this article, the author confirms the hypothesis that covers of contemporary magazines are, in fact, their ‘packaging’. The study also fulfils the following goals: 1) to define the term “packaging”; 2) to discuss the concept of media product packaging; 3) to present the phenomenon of magazine covers as packaging in various theoretical and empirical contexts. The empirical inquiry is based on quantitative and qualitative research. The quantitative research was conducted by the survey method based on CAWI (Computer Assisted Web Interview) technique between the 2nd and the 9th of September 2016, involving a nationwide research sample consisting of Poles. The qualitative research was based on analyses of scholarly sources related to the study of magazine covers, and then on comparison of data situated on magazine covers and data related to packaging when it comes to its function, composition and design.